Insulin-mimetic action of vanadium compounds on osteoblast-like cells in culture - Etcheverry, Susana B. (1997)
Vanadium compounds mimic insulin actions in different cell types. The present study concerns the insulin-like effects of three vanadium(V) derivatives and one vanadium(IV) complex on osteoblast-like (UMR106 and MC3T3E1) cells in culture. The vanadium oxalate and vanadium citrate complexes hydrolyzed completely under the culture conditions, whereas more than 40% of the vanadium tartrate and nitrilotriacetate complexes remained. Vanadate, as well as vanadium oxalate, citrate, and tartrate complexes enhanced cell proliferation (as measured by the crystal violet assay), glucose consumption, and protein content in UMR106 and MC3T3E1 osteoblast-like cells. The vanadium nitrilotriacetate complex (the only peroxo complex tested) stimulated cell proliferation in UMR106 but not in MC3T3E1 cells. This derivative strongly transformed the morphology of the MC3T3E1 cells. All vanadium(V) compounds inhibited cell differentiation (alkaline phosphatase activity) in UMR106 cells. Our data are consistent with the interpretation that vanadium oxalate and citrate complexes hydrolyze to vanadate. Vanadium nitrilotriacetate would appear to be toxic for normal MC3T3E1 osteoblasts. In contrast, the vanadium tartrate complex induced a proliferative effect; however, it did not alter cell differentiation.